2018
DOI: 10.1111/aogs.13336
|View full text |Cite
|
Sign up to set email alerts
|

Development of the TeamOBSPPH – targeting clinical performance in postpartum hemorrhage

Abstract: The TeamOBS-PPH tool appears to be valid and reliable for assessing clinical performance in real-life and simulated settings. The tool will be shared as the free TeamOBS App.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…A further eight studies were identified by checking the references lists. Among these 165 studies, 50 were eligible according to the inclusion criteria (online supplementary table S1),4 5 8 13 21–66 and five of these evaluated the impact of video review in regards to improvement in patient care (PICOS)8 21 23 41 62 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A further eight studies were identified by checking the references lists. Among these 165 studies, 50 were eligible according to the inclusion criteria (online supplementary table S1),4 5 8 13 21–66 and five of these evaluated the impact of video review in regards to improvement in patient care (PICOS)8 21 23 41 62 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The main strength of the study is the unique dataset of videos of the clinical management of patients with real‐life postpartum haemorrhage from two hospitals. Another strength is our systematic assessment of the videos by four raters using the validated tools TeamOBS‐PPH and AOTP with a high inter‐rater agreement.…”
Section: Discussionmentioning
confidence: 99%
“…We included videos of teams managing real‐life patients suffering from major postpartum haemorrhage (≥1000 ml). The videos were recorded at two Danish hospitals: Aarhus University Hospital (level 3) with approximately 5000 deliveries per year, 50 physicians, 100 midwives, and 20 technicians, and the Regional Hospital in Horsens (level 2) with approximately 2000 deliveries per year, 25 physicians, 45 midwives, and two technicians . All delivery rooms were equipped with two or three high‐definition mini‐dome surveillance cameras and a microphone placed in the ceiling in the centre of the room.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations